Integral evaluation process for obtaining pectin and essential oil (2011)
In this work, the extraction of essential oil and pectin from the orange peel (Citrus sinensis) was presented as an integral process. The extraction process was performed using a commercial simulator adapting to the process. Experimental tests were carried out with a kilogram of orange peel processed at the same simulation conditions in order to compare the yields obtained, achieving an acceptable concordance. Subsequently the process was scaled to a ton. As a result, not only the advantages of the integral process are demonstrated, but also the possibility of its implementation at the industrial level. It is also concluded that simulation techniques are a powerful tool that allows to minimize time, costs and experience in the design of processes such as the extraction of essential oil and pectin.